2017
DOI: 10.1016/j.ymssp.2015.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Poles tracking of weakly nonlinear structures using a Bayesian smoothing method

Abstract: This paper describes a method for the identication and the tracking of poles of a weakly nonlinear structure from its free responses. This method is based on a model of multi-channel damped sines whose parameters evolve over time. Their variations are approximated in discrete time by a nonlinear state space model. States are recursively estimated by a new method which couples a two-pass Bayesian estimator with an Expectation-Maximization (EM) algorithm. An iterative procedure between them allows an accurate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…To the best of the authors' knowledge, experiments exhibiting such a large increase in the damping ratio with subsequent decrease are scarce. Stephan et al reported an increase with subsequent decrease in the modal damping ratio for large vibration amplitudes (from about 5.6 % to about 4 %) [14].…”
Section: Nonlinear Modal Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…To the best of the authors' knowledge, experiments exhibiting such a large increase in the damping ratio with subsequent decrease are scarce. Stephan et al reported an increase with subsequent decrease in the modal damping ratio for large vibration amplitudes (from about 5.6 % to about 4 %) [14].…”
Section: Nonlinear Modal Analysismentioning
confidence: 99%
“…A different approach for nonlinear modal testing, suited for both conservative and non-conservative nonlinearities is adopted from modal hammer testing. By analyzing the free decay, amplitude-dependent modal properties are extracted for the vibration levels covered by the free decay [12][13][14]. This approach assumes weak nonlinearity such that modes remain uncoupled, even when several modes are simultaneously excited through impulse forcing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonlinear modal testing refers to obtaining amplitude-dependent modal properties from experimental data. Several researches have proposed to extract modal properties from free decay measurements, either using hammer excitation [9][10][11] or force appropriation with subsequent removal of the excitation [12][13][14]. The signal length of a free decay is inherently limited and depends on the damping.…”
Section: Introductionmentioning
confidence: 99%